Higher LEAP: Learning Area Coordinators’ Leadership Approaches and Faculty Performance in a Philippine University - Robiños, John Robby; Perez, Romelia; Jonas, Edelina (JPAIR Multidisciplinary Research, 2019)
Leadership is a connection between those who aim to influence and those who choose to be influenced and follow. Leaders at all levels practice definite patterns and systems that guide them to perform at their best. The descriptive-correlational study was conducted to identify the most common leadership approaches of learning area coordinators and determine its association with their faculty performance rating. Seventy - six senior high school faculty members were randomly selected to answer an adopted leadership practices inventory instrument developed by Kouzes and Posner. The survey questionnaire measured the learning area coordinators’ level of application of the five leadership approaches. Faculty performance evaluation was also retrieved. Data analysis was carried out using the Chi-square test of correlation. The study findings revealed that learning area coordinators apply the five leadership approaches (modeling the way, inspiring a shared vision, challenging the process, enabling others to act and encouraging the heart) very frequently. Furthermore, about 70% of faculty performed from very satisfactorily to outstanding. Among these leadership approaches, it is modeling the way, challenging the process and encouraging the heart that was associated, X2 (15, 76 = 27.91, 33.66 and 33.11) =24.99, p<.05) to faculty performance evaluation. Based on the findings, recommendations that would enhance and develop leadership styles and practices are given.